AGORAPHOBIA REFLECTED IN ANNA FOX OF THE WOMAN IN THE WINDOW (2021) - Fatimah, Dewi; Christina, Christina (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2023)
This research was conducted to analyze agoraphobia disorder in the main character in the film The Woman in the Window (2021). The researchers use qualitative methods to describe and explain the data. Researcher collect data by watching movies, reading script and reading subtitles from the movie The Woman in the Window. This study aims to finds out the symptoms and how to overcome agoraphobia that the main character. The main character has all three symptoms of agoraphobia, panic attack or anxiety, fear of being in open spaces and fear of being outside the home alone. And the main character has three ways to overcome agoraphobia, consumption of drug, seek professional help and program independently.